Evaluation of the Development Effect of Oilfield Water Injection: Development Unit of Wutonggou Formation in Shannan Oilfield Shachun 5 Block - Wang, Xi (International Journal of Natural Resources and Environmental Studies, 2024)
Shannan Oilfield Shachu 5 block is a typical elastic dissolved gas-driven lithological reservoir, and the underground oil and water distribution is very complicated due to the long-term water injection and drive, and after the implementation of a large number of water injection measures, it is necessary to analyse and evaluate the effect of water-driven development in this block. Through the screening index, the evaluation of water drive development effect is carried out by adopting the water content increase rate, water drive index, water storage rate and control as the main indexes. The evaluation results show that: the main contradiction faced by the reservoir development is that the rate of water content rise is too fast, and the water drive efficiency is low; the main problems faced by the reservoir to improve the water drive effect are the large differences in the distribution of residual oil between layers and wells with low multi-directional efficiency ratio, and the difficulty of water drive excavation in each layer is increased, and so on.